E-124 The characteristics of elderly patients over 80 years of age who underwent mechanical thrombectomy using stent-retrievers due to acute cerebral infarction. (22nd July 2018) - Cho, B; Moon, B; Park, S; Jang, D; Jang, K
Abstract : Introduction: Recently, the average life expectancy of people has increased, and the number of cerebral infarctions in elderly patients over 80 years of age is also increasing. There are increasing cases of mechanical thrombectomy using stent-retriever in elderly patient, but the characteristics and differences of the patient population are not well established yet. The purpose of this study is to investigate the characteristics and prognostic factors of elderly patients over 80 years of age undergoing stent-retriever thrombectomy. Methods: From 2012 to 2017, we analyzed the prospective gathered data of 133 consecutive patients treated with mechanical thrombectomy using stent-retrievers for acute ischemic stroke in a single center. Demographic, clinical, laboratory, and radiologic features of each patient were invasgated. We compared the characteristics of elderly patients over 80 year-old with those of younger patients and evaluated the prognostic factors associated with good outcomes in elderly patients. Results: Of the total 133 patients, 34 patients (25.6%) were over 80 years old. Initial ASPECT score (9.41 vs 8.74, p=0.011), 30 days mRS (4, 21 vs 3.22, p=0.004) and 90 days mRS(4.15 vs 2.99, p=0.001) were significantly higher at elderly patients. Hypertension history (p=0.000), underlying atrial fibrillation (p=0.015), previous anticoagulant or antiplatelet use (p=0.003) were significantly more common in elderly patients. The favorable outcomes (mRS ≤2, p=0.08) were not significantly different between the two groups. Because the 30 days and 90 days mRS were higher in the elderly patients after mechanical thrombectomy, prognosis may be worse and other complications should be noted. Conclusions: Elderly patients over 80 year-old had a few more underlying diseases, and the functional outcome was slightly worse after mechanical thrombectomy using stent retriever in acute cerebral infarction. However, the prognostic factors such as mortality and favorable outcome did not differ significantly between the two groups. Elderly patients should also consider aggressive treatment while appropriately controlling underlying diseases. Disclosures: B. Cho: None. B. Moon: None. S. Park: None. D. Jang: None. K. Jang: None.